Predictive Factors for Farmers’ Knowledge of Social Media for Sustainable Agricultural Development (Indian Journal of Extension Education, 2022)
India is rapidly becoming digitally empowered, transforming the paradigm from paper to digital. Agriculture is not an exception to the availability of information on social media for users, establishing a communication link between farmers, extension agents and agricultural institutions. The study was undertaken in 2021 in the Gandhinagar district of Gujarat State to assess farmers’ knowledge about social media. According to the findings, 65.00 per cent of farmers had a high level of knowledge about social media usage. Education, occupation, annual income, innovativeness, scientific orientation, use of ICT tools, use of social media platforms and information-seeking behaviour were positively and significantly correlated. At the same time, age and farming experience were negatively and significantly related to their knowledge of social media. Thus, to harness the outcome of the current trend of the behaviour of the farmers, policymakers working in the field of farmer capacity building might use the research findings to determine the content and approach of ICT programmes. Also, the results can be considered to create more farmer focused social media platforms.